A finite element analysis of the effects of archwire size on orthodontic tooth movement in extraction space closure with miniscrew sliding mechanics - Jun Kawamura; Naohiko Tamaya (SpringerOpen, 2019)
Abstract Background Sliding mechanics with miniscrews is recently used for extraction space closure. The purpose of this study was to elucidate how and why the archwire size affects long-term tooth movement in miniscrew sliding mechanics. Methods Long-term orthodontic tooth movements were simulated based on a remodeling law of the alveolar bone by using a finite element method, in which the bracket rotated freely within a clearance gap (a play) of the archwire-bracket slot. The archwire size was changed to 0.021, 0.018, and 0.016 in. for the 0.022-in. bracket. Result Lingual crown tipping and extrusion of the incisors increased with decreasing the archwire size. Movements of the posterior teeth were approximately the same irrespective of archwire size. Conclusions When decreasing the archwire size, a play of the archwire-bracket slot, as well as the elastic deformation of the archwire, resulted in lingual tipping of the incisors. This tipping led to extrusion of the incisors.